Aktivitas Jasmani Sebelum Pembelajaran: Alternatif Pembudayaan Gerak Siswa Sekolah Dasar - Hari Amirullah Rachman (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: this objective of this developmental research was to develop physical activities model at lower class (1-3) 10-15 minutes before learning beginning. The field of the research was in the Sekolah Dasar Negeri Percobaan 2 Sleman Yogyakarta. The results of the research was develop physical activities model at lower class (1-3) 10-15 minutes before learning beginning. The model includes locomotor, non locomotor, and stabilization. The model considered the children’s growth and elementary schools’ condition at Yogyakarta.